Photo‐identification as a tool to study small‐spotted catshark Scyliorhinus canicula. Issue 5 (6th April 2018) - Navarro, J.; Perezgrueso, A.; Barría, C.; Coll, M.
Abstract : Photo‐identification (photo‐ID) was tested as a means to identify individual small‐spotted catsharks Scyliorhinus canicula . The spotting pattern of the caudal region of S. canicula was used for the tests and revealed that photo‐ID is an efficient method to identify individuals. Photo‐ID is logistically simple, making it a potential alternative to traditional tagging to provide information on the distribution patterns and population dynamics of S. canicula and related species.